The Unaccompanied Refugee Minors and the Swedish Labour Market - Aycan Celikaksoy; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2015)
More unaccompanied refugee children arrive to and get a residence permit in Sweden than in any other country in Europe. The number of children who arrives is increasing fast. The Swedish experiences are therefore of great interest also for other countries. In this paper we study the labour market situation in terms of employment and income for those who have arrived as unaccompanied minors and have been registered in Sweden. We compare them with those who also arrived as minors from the same countries but who have arrived together with their parents. After controlling for demographic and migration related variables we find that young adults who arrived as unaccompanied refugee children are more likely to be employed than those children who arrived accompanied from the same countries. Another result is that labour market participation is much lower for females than for males. We also compare the labour market situation of these children with that for those who were born in Sweden and are of the same age.
Keywords: J13; J15; J21; J31; 330; unaccompanied minors; refugee children; migration; employment; income